Association of Systolic BP to LVED Pressure Ratio with In-Hospital Mortality in STEMI Patients Undergoing PPCI - Arif, Zeeshan; Shahzad, Syed Khurram; Aslam Khan, Zahoor; Ahmed, Iftikhar; Khan, Masood; Alam, Faiza; Siddiqui , Abdul Hameed (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the association of Systolic Blood Pressure to Left Ventricular End-Diastolic Pressure ratio with in-hospital mortality in ST-Elevation Myocardial Infarction patients undergoing Primary Percutaneous Coronary Intervention.Study Design: Analytical, Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology, National Institute of Heart Diseases, Rawalpindi Pakistan, from Apr-Jun 2023.Methodology: One hundred and ninety-eight patients who underwent Primary Percutaneous Coronary Intervention for ST-Elevation Myocardial Infarction patients presenting within 12-hours were included using non-probability consecutive sampling technique. Patients were divided into two groups (Group-I= SBP/LVEDP ratio ≤4; Group-II= SBP/LVEDP ratio >4). SBP and LVEDP were measured during Primary Percutaneous Coronary Intervention. Demographic and clinical data, including risk factors and laboratory findings, were collected and SBP/LVEDP ratio was calculated. Study variables were compared among groups by applying independent t-test and Chi-square test. p-value4 (Group-II). Group-I showed a higher prevalence of heart failure 5(23.8%), lower ejection fraction (35.48±7.56%), longer duration of in-hospital stay (8.76±2.48 days) (p